Hadith #3866 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; Ahmed bin Ishaq bin al-Husain أحمد بن إسحاق بن الحصين; ibn Abbas; Tawus bin Kaysan طاوس; Uthman bin Muhammad; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
The Prophet (ﷺ) cauterized Sa’d b. Mu’adh from the wound of an arrow.
Grade: Sahih

Hadith #4432 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmed bin Ishaq bin al-Husain أحمد بن إسحاق بن الحصين; Bashyr bin al-Mhajr بشير بن المهاجر; Burayda bin al-Husayb; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري (Sunan Abi Dawud)
A man came to Prophet (ﷺ). He then mentioned a similar tradition but not completely. This version has: People began to speak ill of him but he (the Prophet) forbade them. Then they began to ask forgiveness from him, but he forbade them by saying. He is a man who had committed a sin. Allah will call him to account himself.
Grade: Da'if